PASSIVITY BASED ON ENERGY TANK FOR CARTESIAN IMPEDANCE CONTROL OF DLR SPACE ROBOTS WITH FLOATING BASE AND ELASTIC JOINTS - Le, Luc Tien (Journal of Computer Science and Cybernetics, 2018)
This paper presents a control structure for orbital servicing mission of CEASAR robotic arm developed by German Aerospace Center (DLR). In order to reduce mass the CEASAR arm is equipped with Harmonic-Drives with high ratio which unfortunately lead to high joint elasticity and high motor friction and have to be considered in controller design for successful manipulator in-orbit operations. Therefore, in this control structure, for high tracking control a cascaded position controller based on state feedback control structure with observer-based friction compensation and for safe interaction control with the environment a Cartesian impedance controller is used. The proposed control methods are very efficient and practicable. Furthermore, they are very robust with dynamic parameter uncertainties, coupling dynamics, and can simultaneously provide good results in term of the position accuracy and dynamic behavior. Simulation results validate practical efﬁciency of the controllers.